Improving Psychological and Emotional Well-Being of the First-Year College Students - Robinson, Dyan; Yavuz, Olcay (FIRE: Futuristic Implementations of Research in Education, 2021)
Almost half of the students who begin college are not retained at the institution in which they began. The purpose of this research was to explore the perceptions of first-year college students to improve their psychological and emotional well-being. This quantitative study utilized the College Student Mentoring Scale that includes two interrelated constructs which are, Psychological and Emotional Support and The Existence of a Role Model. The research found that multiple factors impact first-year students' perceptions of their psychological and emotional well-being. Additional findings indicated that response levels were highest for The Existence of a Role Model. It is the intention that this study will add to the somewhat limited research on improving the psychological and emotional well-being of first-year college students in higher education. Also, it will assist in future policies and practices by providing a foundation of the components that influence first-year student success through improving the effectiveness of peer mentoring programs.
Number: 2
Keywords: dept.com; dept.edl; dept.fye; first-year college students; peer-reviewed; ⛔ No DOI found